A NEW REPORT OF TIP BLIGHT AND LEAF SPOT OF ACORUS CALAMUS CAUSED BY NIGROSPORA ORYZAE FROM WEST BENGAL, INDIA - PALASH CHANDRA PAUL; BASUDEB DASGUPTA (The Bioscan, 2014)
Acorus calamus is known as sweet flag (Family: Acoraceae) is a perennial medicinal plant. Found in both temperate and subtemparate zones. Roots and rhizomes are stimulants, emetic, nauseant, stomachic, aromatic, expectorant, carminative, antispasmodic and nervine sedative. Gas chromatography had revealed the presence of two components isolated in pure state i.e. α-asarone and β- asarone. Diseases or pathogens cause deterioration of the active chemicals of the plants which affect the quantitative and qualitative loss of medicinal plants. During a study in the year 2010-2012 at three different locations of West Bengal, India, a new tip blight and leaf spot disease was observed in Acorus calamus caused by Nigrospora oryzae. In Acorus calamus, maximum disease incidence and disease index were recorded during November to February and minimum disease incidence and index of leaf spot or blight by Nigrospora oryzae during May - July, thereafter gradually increased and again reached to the peak during December - January.